2015
DOI: 10.1088/1757-899x/77/1/012009
|View full text |Cite
|
Sign up to set email alerts
|

In-situ deposition of gold nanoparticles onto different substrates by chemical spray pyrolysis

Abstract: Abstract. Au-nanoparticles were deposited in-situ by chemical spray pyrolysis method onto glass and indium tin oxide (ITO) covered glass substrates in the temperature range of 260 to 400 °C. SEM studies showed that the number of Au-NPs increased and the particle size decreased with increasing the deposition temperature. The surface plasmon resonance effect of Au-NPs on glass substrate shifts from 550 to 520 nm with decreasing the mean crystallite size of Au-NPs from 49 to 24 nm. The surface plasmon resonance e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Different techniques have been used to assemble AuNPs on various surfaces in which the stability of AuNPs, interface layer and the support surface are important for the self-organization. Han et al have demonstrated the growth of a single layer AuNPs film deposited on indium tin oxide (ITO) substrate without using an adhesive layer by utilizing diblock copolymer micelle and spin casting technique [18], while Acik et al reported in situ deposition of AuNPs on ITO and glass substrate by using spray pyrolysis (temperature range of 260–400 °C) [19]. Wu et al proposed AuNPs deposition by centrifugation where the thickness depended on centrifugation time [20].…”
Section: Introductionmentioning
confidence: 99%
“…Different techniques have been used to assemble AuNPs on various surfaces in which the stability of AuNPs, interface layer and the support surface are important for the self-organization. Han et al have demonstrated the growth of a single layer AuNPs film deposited on indium tin oxide (ITO) substrate without using an adhesive layer by utilizing diblock copolymer micelle and spin casting technique [18], while Acik et al reported in situ deposition of AuNPs on ITO and glass substrate by using spray pyrolysis (temperature range of 260–400 °C) [19]. Wu et al proposed AuNPs deposition by centrifugation where the thickness depended on centrifugation time [20].…”
Section: Introductionmentioning
confidence: 99%